Cervone, Cristina Maria, and Nicholas Watson, eds. 2023. What Kind of a Thing Is a Middle English Lyric? Philadelphia: University of Pennsylvania Press. Pp. xvi + 546. ISBN 9780812253900. - Putter, Ad (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Cervone, Cristina Maria, and Nicholas Watson, eds. 2023. What Kind of a Thing Is a Middle English Lyric? Philadelphia: University of Pennsylvania Press. Pp. xvi + 546. ISBN 9780812253900.